Upscale production of instant rice porridge with tripe goto - Baguhin, Vilma Saligumba
ABSTRACT This study was under the UP-Phil Rice research project entitled "Rice and Rice-Based Disaster Foods" This study scaled up the production of instant rice porridge with tripe or instant got developed by Mauricio (1999) in response to the increasing demand for convenience food. Scaled up production of instant goto (500 and 1000g) was done in the first phase. The 5 major activities involved: the scaling up of instant rice production, production of instant tripe; production of dehydrated spring onions; comparison of the instant mix and rehydration of the product. Quick cooking rice was prepared by soaking at 50°C for 30 min, steamed under pressure at 121.5°C for 5 min both 500 and 1000g production, dried and forced air convection drying at 45-55°C with an optimum drying times of 90 and 105 min for 500 and 1000g production, respectivly and puffing using oil immersion at 200°C for 1 sec. Selection of the treatments wee based on 100% gelatinization, 100% volume expansion, 100% water absorption, minimal % clumpiness and % breakage, and 8-14% final moisture content. Production of instant tripe involved precooking by boiling in water for 5 min for 2 consecutive times followed by steaming under pressure at 121.5°C for 40 min; lye treatment using boiling 5% lye solution; and dried using forced air convection drying at 65°C for 2.5 and 2.75 for 100 and 500 g production, respectively. Production of dehydrated spring onions involved blanching the fresh leaves using live steam for 2 sec and dehydrated using forced air convection drying at 55°C for 2.75 and 3.33 h for 100 and 500 g production, respectively. The compounded instant got mix was rehydrated by boiling for 5 min using 180 ml water. The consumer acceptability test was determined using 9-point hedonic scale. the t-test for difference at 5% level of significance was used in the analysis of the results. The final product test formulation was slightly to moderately accepted by the panelists. The attributes of the rehydrated instant product were: cream to yellow rice base color, soft to neither soft nor tough consistency, moderate to slightly distinct flavor and aroma and neither soft nor tough tripe texture. The compounded instant goto mix was composed of the quick-cooking rice, dehydrated tripe and spring onions, salt, onion powder, pepper, beef, and meat flavorings, chicken fat, modified starch, fried minced garlic, ground ginger and fish sauce. The compounded and rehydrated instant mix obtained aw values of 0.675 and 0.975, respectively, with corresponding pH values of 6.11 and 6.40. The total Plate Count and the Yeast and Mold Count analysis reported a <10 raise to 2 cfu/g for both the compounded and rehydrated instant products. The price of the instant product with 10% mark up was P12.55 per 49 g which give 180 ml of rehydrated sample.